2012
DOI: 10.1111/j.1749-4486.2012.02532.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of active chronic otitis media comparing courses of eardrops versus one‐off topical treatments suitable for primary, secondary and tertiary healthcare settings

Abstract: This study showed a single application of boric acid powder following external auditory canal irrigation until the perforation was visible to be as effective as the current best practice of topical quinolone eardrops in active chronic otitis media. Boric acid powder is inexpensive and does not require patient compliance. Boric acid powder is a viable, less costly alternative to topical antibiotic/steroid ear drops in the developing world for active chronic otitis media. Acetic acid eardrops 1% are ineffective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 17 publications
(28 reference statements)
4
31
0
Order By: Relevance
“…The microbiology associated with otitis media differed from otitis externa, with P. mirabilis (36%) and P. aeruginosa (33%) being the most common isolates, respectively (Table 1). Our results roughly parallel the microbiology pattern reported by Loock [3] at another tertiary hospital in Cape Town in chronic otitis media patients, namely Proteus spp. (29%), P. aeruginosa (24%) and S. aureus (14%) as the most common.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The microbiology associated with otitis media differed from otitis externa, with P. mirabilis (36%) and P. aeruginosa (33%) being the most common isolates, respectively (Table 1). Our results roughly parallel the microbiology pattern reported by Loock [3] at another tertiary hospital in Cape Town in chronic otitis media patients, namely Proteus spp. (29%), P. aeruginosa (24%) and S. aureus (14%) as the most common.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, MRSA was isolated in only 1 patient (1.7%) with otitis media for 2 years; it is not known what treatment the patient had received at primary care facilities. This is similar to the 1.9% incidence of MRSA reported by Loock [3] in patients with chronic active otitis media. These results differ from reports of changing bacteriological spectra and increases in the incidences of S. aureus and MRSA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This lack of effectiveness of acetic acid has been documented in a recent SA study. [21] CSOM is a condition occurring mainly in patients of low socioeconomic status, [2,12,18] who may not have access to clean water. Exposure of the auditory canals to contaminated water has been identified as a risk factor for CSOM.…”
Section: Discussionmentioning
confidence: 99%
“…In children who suffer associated hearing loss this delay has a negative impact on school performance. [14] In addition, Loock [16] and the aforementioned two local ENT departments investigated the microbial spectrum of otorrhoea in their respective communities. [14][15][16][17] All of the local studies have identified Proteus mirabilis and Pseudomonas aeruginosa as the most prevalent pathogens.…”
mentioning
confidence: 99%